The effect of the silvopastoral system on milk production and reproductive performance of dairy cows and its contribution to adaptation to a changing climate in the drylands of Benin (West-Africa) - Assani Seidou, Alassan; Offoumon, Oyéniran Thierry La Fronde; Sanni Worogo, Sorebou Hilaire; Houaga, Isidore; Koara Yarou, Amoudawenou; Azalou, Maximilien; Adambi Boukari, Foukpe Zhairath; Idrissou, Yaya; Houinato, Marcel; Alkoiret Traoré, Ibrahim (Frontiers in Sustainable Food Systems, 2023)
Knowledge about dairy cows raised in small-scale agroforestry systems in dryland areas is of paramount importance to inform policy and decision making in the dairy production sector in the current context of climate change. The aim of this study was to evaluate the effect of integrated farming systems on daily milk yield and demographic traits of dairy cows in drylands. A study conducted on 447 dairy cows was carried out to compare their milk yield and demographic parameters under different small-scale agroforestry systems in drylands of Benin:Traditional silvopasture (TSS); Improved silvopasture (ISS); Small Integrated Agrosilvopasture (SIAS) and Large Integrated Agrosilvopasture (LIAS). The type of cattle farms had a significant effect (p<0.05) on daily milk yield and demographic traits. Dairy cattle from ISS farms had the highest daily milk yield regardless of the type of dairy cow breed. 7 Demographic traits of herds were significantly (p<0.05) influenced by the type of dairy cattle farms. The proportion of lactating cows was higher (p<0.05) in herds of ISS (48.4%) followed by those in TSS and LIAS (36.1 and 25.0% respectively) while SIAS was the lowest in (14.4%).The pre-weaning mortality rate was higher (p<0.05) in TSS and LIAS farms (18.3 and 17.6 % respectively) compared to SIAS and ISS farms (5.20 and 4.60 % respectively). The fertility rate was higher (p<0.05) in ISS and SIAS farms (92.3 and 89.6% respectively) compared to TSS and LIAS farms (68.3 and 74.2% respectively). The weaning productivity was higher (p<0.05) in ISS and SIAS (88.6 and 85.8 % respectively) than in TSS and LIAS farms (66.1 and 67.6 % respectively). This study showed that ISS farms are characterized by higher milk yield and demographic parameters. ISS systems can then be promoted in smallholder cattle farming to improve milk production and reproductive performance of dairy cows in drylands.